Full-Impact Regulations and the Dormant Commerce Clause - Sears, Will (Columbia Journal of Environmental Law, 2019)
Effective environmental regulation of products requires knowledge of their entire lifespan. For example, a gallon of corn ethanol produces greenhouse gas emissions when burned, but this does not reflect its full environmental impact. The energy and water used to produce the fuel, side effects of production such as land use changes, and emissions associated with its transportation from producers to distributors all add to the environmental impact of the fuel. This holistic method of assessing environmental impacts is known as "lifecycle analysis" or "lifecycle assessment." The scientific community recognizes lifecycle analysis as providing the touchstone for effective environmental regulations. Congress has endorsed this methodology, for example, requiring that federal agencies incorporate lifecycle analysis into contracts to purchase alternative or synthetic fuels. Businesses often employ lifecycle analysis when comparing the environmental impacts of different potential production processes. This Note argues that courts should evaluate full-impact regulations under tier-two of the dormant Commerce Clause framework. State-level full-impact regulations do not implicate the concerns that have traditionally motivated courts to invalidate laws under the dormant Commerce Clause. Properly designed full-impact regulations need not evince a protectionist purpose nor discriminate against out-of-state entities within the meaning of the dormant Commerce Clause. They also need not regulate extraterritorially in the way that the Supreme Court has prohibited. Accordingly, state full-impact regulations challenged on the grounds that they burden interstate commerce should be evaluated under the more deferential balancing test that tier-two regulations receive. This proposed framework preserves the role of district courts in policing the murky boundaries of federal and state authority, while affording states the flexibility they require to design effective environmental regulations.